The ICNALE guide : an introduction to a learner corpus study on Asian learners' L2 English - Ishikawa, Shin'ichiro, 1969- (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Ishikawa provides a practical and extensive guide for the International Corpus Network of Asian Learners of English (ICNALE), a unique dataset including more than 15,000 samples of Asian learners' L2 English speeches and essays. It offers approachable introductions to a variety of corpus studies on the aspects of Asian learners' L2 English. Key topics discussed in the book include: 1)background, aims, and methods of learner corpus research, 2) principles, designs, and applications of the ICNALE, 3) vocabulary, grammar, and pragmatics in Asian learners' L2 English, and 4) individual differences of Asian learners and assessments of their speeches and essays. With many case studies and hands-on guides to utilise ICNALE data to the fullest extent, The ICNALE Handbook is a unique resource for students, teachers, and researchers who are interested in a corpus-based analysis of L2 acquisition"--
Keywords: Corpora (Linguistics); Second language acquisition; English language -- Study and teaching -- Asian speakers; FOREIGN LANGUAGE STUDY / English as a Second Language